Evolving nonlinear impacts of service factors on shared autonomous vehicle service quality - Danting Zhao; Jason Cao; Zhi Dong (Transportation Research Part D: Transport and Environment, 2026)

Structure–function relationship of Konjac glucomannan with varying acetylation degrees in modulating gut microbiota and alleviating prediabetes - Hongchao Wang; Yurong Zhao; Danting Dang; Liming Huang; Zhangming Pei; Jianxin Zhao; Hao Zhang; Wei Chen; Wenjun Wu; Wenwei Lu (Carbohydrate Polymers, 2026)

Comparison research on numerical modeling methods for the passive heat removal system of fast reactors based on PLANDTL benchmark experiment - Haijie Song; Yuhao Zhang; Haiqi Zhao; Danting Sui; Daogang Lu (Annals of Nuclear Energy, 2025)

Microbial community structure in a constructed wetland based on a recirculating aquaculture system: Exploring spatio-temporal variations and assembly mechanisms - Wenjie Tian; Qiufen Li; Zijun Luo; Chao Wu; Bo Sun; Danting Zhao; Saisai Chi; Zhengguo Cui; Ailing Xu; Zhiwen Song (Marine Environmental Research, 2024)

Bioreduction of chromate in a syngas-based membrane biofilm reactor - Chenkai Niu; Xinyu Zhao; Danting Shi; Yifeng Ying; Mengxiong Wu; Chun-Yu Lai; Jianhua Guo; Shihu Hu; Tao Liu (Journal of Hazardous Materials, 2024)

Are Mini and full-size electric vehicle adopters satisfied? An application of the regression with dummy variables - Danting Zhao; Yuandong Liu; Hong Chen (Travel Behaviour and Society, 2024)

Comparing Mini and full-size electric vehicles in China: Evidence from user heterogeneity and satisfaction asymmetry - Shaoxuan Zhu; Danting Zhao; Yihao Li (Journal of Cleaner Production, 2024)

The application and development of electron microscopy for three-dimensional reconstruction in life science: a review - Jingjing Zhao; Xiaoping Yu; Xuping Shentu; Danting Li (Cell and Tissue Research, 2024)

In silico, in vitro and in vivo safety assessment of three Limosilactobacillus mucosae strains for probiotic candidates - Danting Dang; Xiaoming Liu; Haiqin Chen; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2024)

Exploring user satisfaction and improvement priorities in electric vehicle segments - Danting Zhao; Jie Gao; Nieyangzi Liu (Transportation Research Part D: Transport and Environment, 2023)

Interferon-γ enhances the immunosuppressive ability of canine bone marrow-derived mesenchymal stem cells by activating the TLR3-dependent IDO/kynurenine pathway - Jiaqiang Deng; Danting Li; Xiaoya Huang; Weiyao Li; Fangfang Zhao; Congwei Gu; Liuhong Shen; Suizhong Cao; Zhihua Ren; Zhicai Zuo; Junliang Deng; Shumin Yu (Molecular Biology Reports, 2022)

Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ 13 C values ranged from −22.89‰ to −15.86‰, and δ 15 N values ranged from 3.18‰ to 13.57‰, respectively. The δ 13 C and δ 15 N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta . Spatial distribution patterns of zooplankton δ 13 C and δ 15 N values varied in different seasons. Our results suggested that the spatial variation of δ 13 C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ 13 C. In spring, the high phytoplankton biomass might increase the δ 13 C value of small zooplankton in the inner bay. During other seasons, the δ 13 C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13 C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ 13 C and δ 15 N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.

Geochemistry of heavy metal-contaminated sediments from the Four River inlets of Dongting lake, China - Xiaohong Fang; Bo Peng; Zhaoliang Song; Sicheng Wu; Danting Chen; Yafang Zhao; Jing Liu; Yanan Dai; Xianglin Tu (Environmental Science and Pollution Research, 2021)

Fine mapping of S32(t), a new gene causing hybrid embryo sac sterility in a Chinese landrace rice (Oryza sativa L.) - Danting Li; Liangming Chen; Ling Jiang; Susong Zhu; Zhigang Zhao; Shijia Liu; Ning Su; Huqu Zhai; Hiroshi Ikehashi; Jianmin Wan (Theoretical and Applied Genetics, 2007)